POLYMERS: THEIR APPLICATIONS IN DAILY LIFE AND ENVIRONMENTAL ISSUES - Hikmatova Hilola Ilkhom kizi; Nurmamatova Rukhshona Mardi kizi; Khudoyberdiyeva Farzona Ilkhom kizi; Rayimova Zarina Alisher kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Polymers play a crucial role in modern life due to their versatile properties and wide-ranging applications across industries. From packaging and textiles to healthcare and electronics, polymers contribute significantly to daily conveniences. However, their extensive use raises pressing environmental concerns, including pollution, waste management challenges, and ecological impacts. This article explores the dual nature of polymers—highlighting their benefits and the urgent need for sustainable solutions to mitigate environmental damage.